Pengaruh Rasio Likuiditas, Solvabilitas Dan Aktivitas Terhadap Kinerja Keuangan Pada Sub Sektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2021 - Anggun Fathonah; Eka Purnama Sari (Journal of Creative Student Research, 2023)
The main objective of this research is to analyze the relationship between current ratio and return on asset in pharmaceutical companies that are traded on the Indonesia Stock Exchange during the period of 2018-2021. Fristly, throughout the years 2018-2021, the researcher will analyze the correlation between debt to asset ratio and ROA in the pharmaceutical industry segment of the Indonesia Stock Exchange. The purpose of this study includes three main goals: (2) to determine the effect of total asset turnover on return on asset of pharmaceutical companies on the Indonesia Stock Exchange from 2018 to 2021; and (3) to determine the effect of current ratio, debt to assets ratio, and total asset turnover on return on assets of pharmaceutical companies on the Indonesia Stock Exchange from 2019 to 2021. This research employs a quantitative approach, and 12 different businesses are presented as the sample. Tools used to describe and analyze data include multiple linear regression analysis. Based on the data, the results show that current ratio does not have a significant effect on Return On Assets (Sig = 0.554), Debt To Assets Ratio does not have a significant effect on Return On Assets (Sig = 0.097), Total Asset Turnover does not have a positive and significant effect on Return On Assets (Sig = 0.566), and the combination of all three factors has a positive and significant effect on Return On Assets.